Macro-anatomical investigations on the skeletons of mole-rat (Spalax leucodon Nordmann) III. Skeleton axiale - Özkan, Zait Ender (My University, 2007)
The average length and height of the skull were 42.5 mm and 15.7 mm, respectively. The height of the skull was approximately 37% of the length of the skull in mole-rats (Spalax leucodon Nordmann). The average greatest breadth and the greatest height of the for. magnum were 6.9 mm and 6.1 mm, respectively. The dental formula on one half of the upper and lower jaw was I1, C0, P0, M3 / I1, C0, P0, M3. Arcus zygomaticus was well developed and formed by the proc. zygomaticus of os temporale, the proc. temporalis of os zygomaticum and a third small bone (jugal). The third bone was not fused with the other processes forming the arcus zygomaticus. The two halves of the mandibula were not fused. There were four processes of the ramus mandibulae: proc. angularis, proc. coronoideus, proc. condylaris and the fourth process lodging the lower incisor tooth. The vertebral formula was found as C7, T13, L6, S4, Ca5. Cranial articular processes of the first caudal vertebrae were present. There were rudimentary cranial articular processes on the second caudal vertebrae and cranial articular processes were absent on all other caudal vertebrae. Caudal articular processes were not present on all caudal vertebrae.
Keywords: Axial skeleton; Mole-rat; Spalax leucodon nordmann